1992
DOI: 10.1111/j.1469-8137.1992.tb01092.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and excretion of sodium, potassium and chloride from leaves of two accessions of Diplachne fusca (L.) Beauv.

Abstract: SUMMARYWhen two accessions of brown beetle grass [Diplachne fusca (L.) Beauv. syn. Leptochloa fusca (L.) Kunth], differing in tolerance to salinity, were exposed to NaCl over 15 d, Na concentrations were constant in the shoot. However, there were differences in shoot Na concentration between the two accessions which were manifest after 5 d exposure to 100 mol m~^ NaCl. Na and Cl concentrations in the shoot were found to be controlled within a narrow range and did not increase any further after 5 d exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The same result was also found on K + uptake in shoots and stems of Baccaurea parviflora [35] and Atriplex hortensis [53]. Halophytes maintain or increase K + selectivity under high salt stress through three possible mechanisms for salt tolerant: salt exclusion from leaves and stems, prevention of Na + loading into the xylem, and prevention of Na + absorbing from roots [10,19,51]. Our results of low Na + content in root and shoot biomass and the existence of salt glands on Red River leaves and stems suggest that Red River has at least one or more these salt-tolerance mechanisms.…”
Section: Discussionsupporting
confidence: 65%
“…The same result was also found on K + uptake in shoots and stems of Baccaurea parviflora [35] and Atriplex hortensis [53]. Halophytes maintain or increase K + selectivity under high salt stress through three possible mechanisms for salt tolerant: salt exclusion from leaves and stems, prevention of Na + loading into the xylem, and prevention of Na + absorbing from roots [10,19,51]. Our results of low Na + content in root and shoot biomass and the existence of salt glands on Red River leaves and stems suggest that Red River has at least one or more these salt-tolerance mechanisms.…”
Section: Discussionsupporting
confidence: 65%
“…The ability to regulate Na + or Cl − uptake and transport to the shoot is crucial for salt resistance in plants (Greenway and Munns 1980;Tester and Davenport 2003;Warwick and Halloran 1992). Under natural condition Na + and Cl − concentrations are higher in sheaths than in leaf blades of, for example, Diplachne fusca (L.) Beauv., indicating that the species has the capacity to sequester high levels of Na + and Cl − in the sheath away from the leaf blade as well as maintaining a high selectivity for K + over Na + (Warwick and Halloran 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to regulate Na + or Cl − uptake and transport to the shoot is also crucial for salt tolerance in plants (Greenway and Munns 1980, Munns 2005, Tester and Davenport 2003, Warwick and Halloran 1992;). It has been shown that Cl − ‘exclusion’ is a key trait for salt tolerance in Lotus tenuis (Teakle et al 2007).…”
Section: Discussionmentioning
confidence: 99%